2013
DOI: 10.1002/hyp.9655
|View full text |Cite
|
Sign up to set email alerts
|

Influence of inclination and permeability of solitary woody riparian plants on local hydraulic and sedimentary processes

Abstract: The role of solitary woody riparian plants with respect to local erosion and deposition of sediments is investigated. A focus is laid on the characteristics ‘inclination’ and ‘permeability’ of the plant's projected frontal area. Therefore, two experimental studies using cylindrical obstacles were carried out in a laboratory flume, one aiming at inclination, the other at permeability. The first series revealed that the total amount of mobilized sediment around the cylinder on average decreased by 8–10% per 5° i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 38 publications
(73 reference statements)
1
19
0
Order By: Relevance
“…In addition, a depositional ridge was observed in this study along the patch's lateral edge, which was particularly clear under the experimental conditions in Case 2 (Figure ). This depositional ridge was consistent with field observations made during a flood (Rodrigues et al ., ; Euler et al ., ). Several field studies found that trees and shrubs promote leeside sediment deposition during floods, which encourages the colonization of vegetation (Gurnell and Petts, ; Euler et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a depositional ridge was observed in this study along the patch's lateral edge, which was particularly clear under the experimental conditions in Case 2 (Figure ). This depositional ridge was consistent with field observations made during a flood (Rodrigues et al ., ; Euler et al ., ). Several field studies found that trees and shrubs promote leeside sediment deposition during floods, which encourages the colonization of vegetation (Gurnell and Petts, ; Euler et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…Digital elevation models (Fig. 6) show a relatively plane surface of the bar in 2007 with superimposed low-amplitude longitudinal obstacle marks (Nakayama et al, 2002;Rodrigues et al, 2007;Euler and Herget, 2011;Euler et al, 2014) caused by the presence of patches of young trees.…”
Section: Topographical and Morphological Evolution Of The Barmentioning
confidence: 99%
“…Thin layers of fine sediments (mainly silts) enriched in organic matter and penetrated by roots are found in the densely vegetated areas (C12 and C22). These thin layers are markers of emersion phases and fixing of sediments by pioneer trees or herbs growing on obstacle marks (Rodrigues et al, 2007;Euler et al, 2014).…”
Section: Scour-and-fill Processes On the Barmentioning
confidence: 99%
See 2 more Smart Citations